ASSOCIATION BETWEEN INTRAOPERATIVE GOAL-DIRECTED FLUID THERAPY AND SURGICAL SITE INFECTION RATES IN GASTROINTESTINAL SURGERY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Surgical site infection (SSI) is still a common complication of gastrointestinal surgery. Wound healing can be affected by tissue hypoperfusion, fluid overload, vasoconstriction, oedema and impaired oxygen delivery. The aim of this study was to assess the relationship between the use of goal-directed fluid therapy (GDFT) and 30-day SSI following elective gastrointestinal surgery. Methods: This was a prospective observational study of 312 adults who were undergoing elective gastrointestinal surgery. Patients treated with stroke-volume guided intraoperative GDFT (n=154) were compared to patients who received conventional fluid therapy (n=158). Dynamic haemodynamic monitoring with crystalloid bolus was only performed if stroke volume rose by at least 10% following a fluid challenge, and vasopressors were used to maintain mean arterial pressure. The primary outcome was CDC-defined SSI within 30 days. Secondary outcomes were total complications, anastomotic leak, postoperative ileus, acute kidney injury, lactate clearance, length of stay, and readmission. Results: Baseline characteristics, diabetes, smoking, albumin, surgical wound class and procedure complexity were similar between the groups. The GDFT group received less crystalloid (2.1 +/- 0.7 vs. 3.2 +/- 1.1 L, p